The Origin of Silica of Marine Shale in the Upper Ordovician Wulalike Formation, Northwestern Ordos Basin, North China - Zhang, Yanni; Li, Rongxi; Huang, Hexin; Gao, Tian; Chen, Lei; Zhao, Bangsheng; Wu, Xiaoli; Khaled, Ahmed (Frontiers in Earth Science, 2021)
The shale of the Wulalike Formation developed in the northwestern Ordos Basin is considered to be an effective marine hydrocarbon source rock. One of the key factors for successful shale gas exploration in the Wufeng–Longmaxi Formation in the Sichuan Basin is the high content of biogenic silica. However, few people have studied the siliceous origin of the Wulalike shale. In this study, we used petrographic observation and element geochemistry to analyze the origin of silica in the Wulalike shale. The results show that the siliceous minerals are not affected by hydrothermal silica and mainly consist of biogenic and detrital silica. A large number of siliceous organisms, such as sponge spicules, radiolarians, and algae, are found under the microscope. It has been demonstrated that total organic carbon has a positive correlation with biogenic silica and a negative correlation with detrital silica, and biogenic silica is one of the effective indicators of paleoproductivity. Therefore, the enrichment of organic matter may be related to paleoproductivity. Through the calculation of element logging data in well A, it is found that biogenic silica is mainly distributed in the bottom of the Wulalike Formation, and the content of biogenic silica decreases, while the content of detrital silica increases upward of the Wulalike Formation. Biogenic silica mainly exists in the form of microcrystalline quartz, which can form an interconnected rigid framework to improve the hardness and brittleness of shale. Meanwhile, biogenic microcrystalline quartz can protect organic pores from mechanical compaction. Therefore, it may be easier to fracture the shale gas at the bottom of the Wulalike Formation in well A.